Identification of Neuroblastoma Subgroups Based on Three-Dimensional Telomere Organization - Alexandra Kuzyk; John Gartner; Sabine Mai (Translational Oncology, 2016)
Using 3D telomere quantitative fluorescence in situ hybridization, we determined the 3D telomere organization of 74 neuroblastoma tissue samples. Hierarchical cluster analysis of the measured telomere parameters identified three subgroups from our patient cohort. These subgroups have unique telomere profiles based on telomere length and nuclear architecture. Subgroups with higher levels of telomere dysfunction were comprised of tumors with greater numbers of telomeres, telomeric aggregates, and short telomeres (P < .0001). Tumors with greater telomere dysfunction were associated with unfavorable tumor characteristics (greater age at diagnosis, unfavorable histology, higher stage of disease, MYCN amplification, and higher MYCN expression) and poor prognostic risk (P < .001). Subgroups with greater telomere dysfunction also had higher intratumor heterogeneity. MYCN overexpression in two neuroblastoma cell lines with constitutively low MYCN expression induced changes in their telomere profile that were consistent with increased telomere dysfunction; this illustrates a functional relationship between MYCN and 3D telomere organization. This study demonstrates the ability to classify neuroblastomas based on the level of telomere dysfunction, which is a novel approach for this cancer.